Raman fingerprint of two terahertz spin wave branches in a two-dimensional honeycomb Ising ferromagnet. Issue 1 (December 2018) - Jin, Wencan; Kim, Hyun; Ye, Zhipeng; Li, Siwen; Rezaie, Pouyan; Diaz, Fabian; Siddiq, Saad; Wauer, Eric; Yang, Bowen; Li, Chenghe; Tian, Shangjie; Sun, Kai; et al.
Abstract Two-dimensional (2D) magnetism has been long sought-after and only very recently realized in atomic crystals of magnetic van der Waals materials. So far, a comprehensive understanding of the magnetic excitations in such 2D magnets remains missing. Here we report polarized micro-Raman spectroscopy studies on a 2D honeycomb ferromagnet CrI3 . We show the definitive evidence of two sets of zero-momentum spin waves at frequencies of 2.28 terahertz (THz) and 3.75 THz, respectively, that are three orders of magnitude higher than those of conventional ferromagnets. By tracking the thickness dependence of both spin waves, we reveal that both are surface spin waves with lifetimes an order of magnitude longer than their temporal periods. Our results of two branches of high-frequency, long-lived surface spin waves in 2D CrI3 demonstrate intriguing spin dynamics and intricate interplay with fluctuations in the 2D limit, thus opening up opportunities for ultrafast spintronics incorporating 2D magnets. Characteristics of spin waves in recently discovered two-dimensional (2D) Ising ferromagnets are still lacking. Here, Jin and Kim et al. report Raman resonance evidence of two sets of surface spin waves in the 2D honeycomb ferromagnet CrI3 .